2019
DOI: 10.1093/ibd/izz001
|View full text |Cite
|
Sign up to set email alerts
|

Real-world Pattern of Biologic Use in Patients With Inflammatory Bowel Disease: Treatment Persistence, Switching, and Importance of Concurrent Immunosuppressive Therapy

Abstract: Background and aims Medication persistence, defined as the time from drug initiation to discontinuation of therapy, has been suggested as a proxy for real-world therapeutic benefit and safety. This study seeks to compare the persistence of biologic drugs among patients with inflammatory bowel disease (IBD). Methods Patients with newly diagnosed IBD were included in a retrospective study using Truven MarketScan database. Treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
111
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(127 citation statements)
references
References 15 publications
13
111
3
Order By: Relevance
“…A realworld study of TNF-inhibitors (ADA, CZP, IFX) reported that 38-45% of CD patients discontinued their anti-TNF therapy within 12 months [19]. Another recently published real-world study reported that only 48.5% of the CD [34]. The present UST study found that most CD patients were persistent, and 83.6% remained persistent 1 year after initiation of UST.…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…A realworld study of TNF-inhibitors (ADA, CZP, IFX) reported that 38-45% of CD patients discontinued their anti-TNF therapy within 12 months [19]. Another recently published real-world study reported that only 48.5% of the CD [34]. The present UST study found that most CD patients were persistent, and 83.6% remained persistent 1 year after initiation of UST.…”
Section: Discussionsupporting
confidence: 41%
“…Further studies comparing UST to other biologics are needed to assess persistence rates over more extended follow-up periods. The most common reasons for discontinuation of biologic treatment among CD patients include disease progression, loss of response, and infection events [34]. The high real-world persistence we found in the current study suggests effectiveness of UST 1 year after initiation.…”
Section: Discussionmentioning
confidence: 50%
“…Vedolizumab was discontinued in 72% at 2 years. This is consistent with large real‐world data for other biologics . In this refractory population, the majority of discontinuation is explained by need for colectomy.…”
supporting
confidence: 88%
“…As the analysis focused on persistence during maintenance in patients who had completed the induction phase of biologic therapy without switching or discontinuing treatment, differences in the duration of induction between the two biologics were not considered to be relevant. [27][28][29][30][31][32][33] The risk of hospitalization would not be expected to increase in the combination subgroups given that there were no significant differences in treatment persistence among the three subgroups. 25,26 Our results indicate that in UC, step-up from a single-agent IM to biologic/IM combination treatment (in the Bio + prior IM subgroup) may be better maintained over the long term than biologic monotherapy if infliximab is chosen.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with previous data. [27][28][29][30][31][32][33] The risk of hospitalization would not be expected to increase in the combination subgroups given that there were no significant differences in treatment persistence among the three subgroups. A previous US claims analysis has shown an increase in hospitalizations for UC patients without therapeutic persistence to infliximab.…”
Section: Discussionmentioning
confidence: 99%